Susceptibility of Nrf2-Null Mice to Steatohepatitis and Cirrhosis upon Consumption of a High-Fat Diet Is Associated with Oxidative Stress, Perturbation of the Unfolded Protein Response, and Disturbance in the Expression of Metabolic Enzymes but Not with Insulin Resistance - Meakin, Paul J.; Chowdhry, Sudhir; Sharma, Ritu S.; Ashford, Fiona B.; Walsh, Shaun V.; McCrimmon, Rory J.; Dinkova-Kostova, Albena T.; Dillon, John F.; Hayes, John D.; Ashford, Michael L. J. (Molecular and cellular biology, 2014)
Mice lacking the transcription factor NF-E2 p45-related factor 2 (Nrf2) develop more severe nonalcoholic steatohepatitis (NASH), with cirrhosis, than wild-type (Nrf2 +/+ ) mice when fed a high-fat (HF) diet for 24 weeks. Although NASH is usually associated with insulin resistance, HF-fed Nrf2 −/− mice exhibited better insulin sensitivity than HF-fed Nrf2 +/+ mice. In livers of HF-fed mice, loss of Nrf2 resulted in greater induction of lipogenic genes, lower expression of β-oxidation genes, greater reduction in AMP-activated protein kinase (AMPK) levels, and diminished acetyl coenzyme A (CoA) carboxylase phosphorylation than in the wild-type livers, which is consistent with greater fatty acid (FA) synthesis in Nrf2 −/− livers. Moreover, primary Nrf2 −/− hepatocytes displayed lower glucose and FA oxidation than Nrf2 +/+ hepatocytes, with FA oxidation partially rescued by treatment with AMPK activators. The unfolded protein response (UPR) was perturbed in control regular-chow (RC)-fed Nrf2 −/− mouse livers, and this was associated with constitutive activation of NF-κB and JNK, along with upregulation of inflammatory genes. The HF diet elicited an antioxidant response in Nrf2 +/+ livers, and as this was compromised in Nrf2 −/− livers, they suffered oxidative stress. Therefore, Nrf2 protects against NASH by suppressing lipogenesis, supporting mitochondrial function, increasing the threshold for the UPR and inflammation, and enabling adaptation to HF-diet-induced oxidative stress.